Unsicherheit der Verteilungs- und Armutspolitik im ökonomischen Transformationsprozess - Diehl, Martin; Justus Liebig University Giessen (My University, 2006)
Die Arbeit stellt die Unsicherheit der Verteilungs- und Armutspolitik im ökonomischen Transformationsprozess systematisch dar. Es wird gezeigt, dass die Zielunsicherheit, die Datenunsicherheit sowie die Modellunsicherheit der Verteilungspolitik Implikationen für die Umsetzung, Konzeption und Zielformulierung der Verteilungs- und Armutspolitik bedingen. Die der Verteilungs- und Armutspolitik implizite Unsicherheit ist ausgeprägter als die der Allokations- oder der Stabilitätspolitik. Abschließend werden allgemeine Implikationen für die Verteilungs- und Armutspolitik abgeleitet.

The dissertation analyses systematicly the uncertainties for distributional policies and poverty alleviation during the economic transition process. It is shown that the indetermination of the policy objectives, the uncertainties in distributional datas and poverty data as well as the uncertainty of respective models demand implications for implementation, concepts and for the formulation of policy objectives. The implicit uncertainty in distributional policies is more pronounced than the respective uncertainty of allocational or stabilizational policies. Concluding, the author derives generell implications for distributional policies as well as poverty alleviation.
Keywords: Verteilungspolitik; Armutspolitik; Transformation; Unsicherheit; distribution; poverty; transition process; uncertainty; ddc:330